KAJIAN PENERAPAN ARSITEKTUR EKOLOGI PADA ULAMAN ECO-LUXURY RESORT - Haikhal Al Habib; Dominikus Aditya Fitriyanto (Jurnal Arsitektur ARCADE, 2024)
Abstract: The development of Indonesia's tourism sector plays an important role in advancing the economy and state income through creating job opportunities for local residents as well as increasing state foreign exchange earnings through the accommodation sector. Activities in resort hotel operations cannot be separated from the use of energy sources to facilitate facility performance as well as the disposal of waste and uncontrolled carbon emissions. Resorts as accommodation are generally located in areas that have strategic locations, including on the coast, mountains, hills, riverbanks, and forests, so that these areas require that environmental control be implemented, human involvement as actors, and building control in constructing buildings. comfortable, minimize the use of energy from excessive sources, and reduce the negative impact of building design on the environment. This journal uses qualitative research methods with library sources based on the internet. Based on its important function, it is hoped that Eco Ulaman Eco Luxury Resort can plan ecological architecture for accommodation that is comfortable to live in. Keyword: Ecology Architecture, Environment, Resort.Abstrak: Pengembangan sektor pariwisata Indonesia berperan penting dalam memajukan ekonomi dan pendapatan negara melalui penciptaan peluang kerja bagi penduduk lokal serta meningkatkan penerimaan devisa negara dengan sektor akomodasi. Aktivitas dalam operasional hotel resort tidak lepas dari penggunaan sumber energi untuk memudahkan kinerja fasilitas serta pembuangan limbah dan emisi karbon yang tidak terkontrol. Resort sebagai akomodasi ini umumnya berada di daerah yang memiliki letak kawasan strategis antara lain di tepi pantai, pegunungan, perbukitan, tepi sungai, dan hutan sehingga mengharuskan kawasan ini menerapkan perancangan yang pengendalian lingkungan, keterlibatan manusia sebagai pelaku, dan pengendalian bangunan dalam membangun bangunan yang nyaman, meminimalisir penggunaan energi dari sumber yang berlebihan, dan mengurangi dampak buruk dalam merancangan bangunan terhadap lingkungan. Jurnal ini menggunakan metode penelitian kualitatif dengan sumber pustaka berdasarkan dari internet. Berdasarkan fungsinya penting diharapkan Eco Ulaman Eco luxury Resort dapat merencanakan arsitektur ekologi untuk penginapan yang nyaman untuk dihuni.Kata Kunci: Arsitektur Ekologi, Lingkungan, Resort.